Comparing the Efficacy of Transcutaneous Electric Nerve Stimulation (TENS) and Low Level Laser Therapy (LLLT) in the Management of Temporomandibular Joint Disorders: A Pilot Study - Vishalini Kalaivanan; Alex M. Muruppel; Angeline Deepthi; E. Gracelin Ranjitha; J. John Hearty Deepak; Kandasamy Murugan (Journal of Indian Academy of Oral Medicine and Radiology)
Background: TMJ disorder is a common presenting condition in the dental clinic. There are various treatment modalities for the management of TMD. No specific therapy has proven its superiority over other therapies. However, the noninvasive procedures are safe and patient friendly with no side effects. Hence, we compared the efficacy of TENS and LLLT in this study. Objectives: To compare and evaluate the efficacy of TENS and LLLT in the treatment of TMJ disorder. To reduce pain intensity, muscular tenderness, and improve the mouth opening. Methods: Ten patients with TMJ symptoms coming under the Groups I and II of research diagnostic criteria are included in the study. The study was done as split mouth technique, where TENS was performed in one side and LLLT was performed in another side of the TMJ. Both the therapies were performed in a total of 9 sessions in alternative days. Pain intensity was measured using VAS before and after the procedure for each session and recorded. Statistical evaluation was done by using SPSS version 22 [using ANOVA and Mann–Whitney test (P < 0.05)]. Results: Analyzing the pain intensities of both groups using VAS score at the end of each session showed statistically significant changes in pain reduction. Conclusion: Both therapies were effective in the treatment of TMJ disorder. However, LLLT is more efficient than transcutaneous electric nerve stimulation.